2019
DOI: 10.1002/anie.201908490
|View full text |Cite
|
Sign up to set email alerts
|

Thuricin Z: A Narrow‐Spectrum Sactibiotic that Targets the Cell Membrane

Abstract: Sactionine-containing antibiotics (sactibiotics) are ag rowing class of peptide antibiotics belonging to the ribosomally synthesized and post-translationally modified peptide (RiPP) superfamily.W er eport the characterization of thuricin Z, an ovel sactibiotic from Bacillus thuringiensis. Unusually,t he biosynthesis of thuricin Zi nvolves two radical S-adenosylmethionine (SAM) enzymes,T hzC and ThzD. Although ThzC and ThzD are highly divergent from each other,these two enzymes produced the same sactionine ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 51 publications
(25 reference statements)
2
37
0
2
Order By: Relevance
“…, thurincin H from Bacillus thuringiensis SF361, the twopeptide thuricin CD from the human fecal isolate B. thuringiensis DPC 6431, and huazacin or thuricin Z from B. thuringiensis serovar Huazhongensis)(25,32,93,94). They have been found recently in Ruminococcus (ruminococcins from Ruminococcus gnavus isolated from the human microbiota)(32,33) and presumably in Staphylococcus (hyicin from Staphylococcus hyicus 4244).…”
mentioning
confidence: 99%
“…, thurincin H from Bacillus thuringiensis SF361, the twopeptide thuricin CD from the human fecal isolate B. thuringiensis DPC 6431, and huazacin or thuricin Z from B. thuringiensis serovar Huazhongensis)(25,32,93,94). They have been found recently in Ruminococcus (ruminococcins from Ruminococcus gnavus isolated from the human microbiota)(32,33) and presumably in Staphylococcus (hyicin from Staphylococcus hyicus 4244).…”
mentioning
confidence: 99%
“…We aim to reveal in detail their biosynthetic pathways (many involve radical SAM enzymes), to discover novel bioactive compounds by genome mining and by bioengineering, and to decipher their modes of action. [5][6][7] www.cjc.wiley-vch.de…”
mentioning
confidence: 99%
“…Next to BeiA is a radical SAM protein Cbei_4157 (hereafter BeiB) (Figure 1B), which should be responsible for BeiA modification. To validate the function of BeiB, we co‐expressed BeiA and BeiB in E. coli by following the procedures reported previously, [ 1,23,24 ] and BeiA was also expressed alone in E. coli for comparative analysis. High resolution mass spectrometry (HR‐MS) analysis revealed that BeiA obtained from co‐expression with BeiB is 2 Da less than BeiA expressed alone, suggesting formation of a thioether crosslink ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%